Chemopreventive effects of angiotensin II receptor type 2 agonist on prostate carcinogenesis by the down-regulation of the androgen receptor - Ito, Yusuke (Oncotarget, 2018)
We recently reported that angiotensin II receptor blockers (ARBs) have chemopreventive and chemotherapeutic potential against prostate cancer via the reduction of androgen receptor (AR) expression. In this study, we investigated the effects of the angiotensin II receptor type 2 (AT2R) agonist Compound 21 (C21), which is expected to play similar roles to an ARB, on prostate carcinogenesis using the transgenic rat for adenocarcinoma of prostate (TRAP) model previously established in our laboratory. In vitro analyses of the cell growth, Western blotting and reporter gene assays were performed using LNCaP cells. TRAP rats at 6 weeks of age were randomly divided into 3 groups of 12 animals each and treated with C21 at 1 or 2 mg/kg/day in drinking water for 12 weeks. C21 reduced the proliferation activity of prostate cancer cells and down-regulated the PSA promoter activity and the AR protein expression. We discovered that C21 inhibited the progression of prostate carcinogenesis in TRAP rats and decreased the incidence of adenocarcinoma in the lateral prostate. A significant increase in the apoptotic index with activation of caspase 3 and 7 were observed by immunohistochemistry and Western blotting analyses. C21 also down-regulated the expression of AR significantly in TRAP rat prostate. C21 decreased the expression of AR and reduced the proliferation activity effectively in prostate cancer cells and TRAP rat prostate. These findings suggest that AT2R agonist may be a candidate novel chemopreventive agent against human prostate cancer.